1980
DOI: 10.1111/j.1423-0410.1980.tb02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Blood Donors for High Titre Antibody to Herpes Varicella‐Zoster

Abstract: As a method of increasing supplies of varicella-zoster immunoglobulin, semi-automated screening of blood donors for high titre complement-fixing antibody was initiated. This was compared with the previously used method of donor selection based on a history of varicella or zoster in the past 6 months. About one-third of the "history" donors had titres of greater than or equal to 1 in 64 and generally these levels declined rapidly. In contrast, although only 1.1% of donors in random screening had antibody titres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The source of VZVIG or VZVIP, however, is limited, because they have been obtained from the blood of convalescents from herpes zoster infection. Hejjas et al (1980) reported that 1% of blood donors had a high titer of antibody to VZV (higher than 64 units) by complement fixation (CF) test. …”
mentioning
confidence: 99%
“…The source of VZVIG or VZVIP, however, is limited, because they have been obtained from the blood of convalescents from herpes zoster infection. Hejjas et al (1980) reported that 1% of blood donors had a high titer of antibody to VZV (higher than 64 units) by complement fixation (CF) test. …”
mentioning
confidence: 99%